Green product quality: A gray servqual approach - Muhammad Fajar Rizaldi; Hendri Andi Mesta (Universitas Negeri Padang, 2021)
This study aims to determine the quality of LED lights from the point of view of consumers in the city of Padang.This type of research is descriptive research. The population of this research is the users of LED lights in the city of Padang, which requires 130 people. In this study the number of samples was determined using a random sampling technique. Random sampling with an equal chance of being selected. Research using the Gray Servqual method, using the Gray Servqual method can be used to solve the problem of uncertainty in cases with little data and incomplete information. From the analysis of these results, it can be seen how the quality of LED lights according to the consumer's point of view. The results of this study indicate that the quality of the LED lamps is good, but there are several attributes that need to be tried to make improvements.